RAS, Cellular Plasticity, and Tumor Budding in Colorectal Cancer - Maffeis, Valeria; Nicolè, Lorenzo; Cappellesso, Rocco (Frontiers in Oncology, 2019)
The high morbidity and mortality of colorectal cancer (CRC) remain a worldwide challenge, despite the advances in prevention, diagnosis, and treatment. RAS alterations have a central role in the pathogenesis of CRC universally recognized both in the canonical mutation-based classification and in the recent transcriptome-based classification. About 40% of CRCs are KRAS mutated, 5% NRAS mutated, and only rare cases are HRAS mutated. Morphological and molecular correlations demonstrated the involvement of RAS in cellular plasticity, which is related to invasive and migration properties of neoplastic cells. RAS signaling has been involved in the initiation of epithelial to mesenchymal transition (EMT) in CRC leading to tumor spreading. Tumor budding is the morphological surrogate of EMT and features cellular plasticity. Tumor budding is clinically relevant for CRC patients in three different contexts: i) in pT1 CRC the presence of tumor buds is associated with nodal metastasis, ii) in stage II CRC identifies the cases with a prognosis similar to metastatic disease, and iii) intratumoral budding could be useful in patient selection for neoadjuvant therapy. This review is focused on the current knowledge on RAS in CRC and its link with cellular plasticity and related clinicopathological features.